Evaluation of climate change impacts and effectiveness of adaptation options on nitrate loss, microbial respiration, and soil organic carbon in the Southeastern USA. (October 2021) - Lychuk, Taras E.; Hill, Robert L.; Izaurralde, Roberto C.; Momen, Bahram; Thomson, Allison M.
Abstract: CONTEXT: Climate change presents an agricultural challenge in the Southeastern USA with implications for maintaining environmental quality. OBJECTIVE: The objective of this study was to assess climate change impacts and adaptation practices (biochar and irrigation) simulated with the Environmental Policy Integrated Climate (EPIC) model on nitrate-N (NO3 -N) losses, microbial respiration (MR) and soil organic carbon (SOC) in the Southeastern USA. METHODS: The EPIC model was used to assess the impacts of climate change and adaptations on NO3 -N losses in leachate and runoff from the soil profile (0–100 cm), loss of soil C via MR (0–100 cm), and impacts on SOC stocks (0–10 cm) for representative farms growing C3 and C4 crops within ten Southeastern USA states. The adaptations explored were annual biochar applications and irrigation. Historical baseline (1979–2009) and future (2041–2070) climate scenarios were used for simulations with CO2 concentrations of 360 ppm and 500 ppm, respectively. Four regional climate models (RCMs), nested within global climate models (GCMs) for their boundary conditions, simulated changes in air temperatures, precipitation, and solar radiation. RESULTS AND CONCLUSIONS: Climate change increased simulated NO3 -N losses in leaching and runoff by 40–80%, compared to historical baseline scenarios that was attributed to overall increased annual precipitation under three of the four RCM_GCM models. For the C4 crops, NO3 -N leaching and runoff losses were 16–47% and 31–45% lower than for the C3 crops, respectively. Biochar applications reduced NO3 -N leaching in the West region during 2066–2070 under the RCM3_CGCM3 model. The differences in MR between the C4 and C3 crops ranged from 3 to 75%. SOC increased under C4 crops and when biochar was applied. We concluded that inclusion of C4 crops in crop rotations and the applications of biochar under wetter climate scenarios may be a promising adaptation strategy to reduce NO3 -N losses and increase SOC content in the soils of the Southeastern USA. SIGNIFICANCE: This study represents one of the first attempts to assess the effectiveness of climate change adaptations such as the agricultural use of biochar and irrigation. The findings from this study strongly contribute to our understanding of potential climate change impacts on a region's agriculture and resulting environmental footprint. This information may be used by the scientific community along with decision and policy makers working on conceptual and practical technologies to mitigate the impacts of climate change on agriculture and the environment. Graphical abstract: Unlabelled Image Highlights: Climate change presents a challenge for agriculture in the Southeastern USA with implications to environmental quality The objective of this study was to assess effects of climate change and adaptations on nitrate loss, microbial respiration and soil organic carbon Future nitrate loss increased by 40–80% and was lower with biochar and under C4 than C3 crops; carbon was higher under C4 crops and with biochar Inclusion of C4 crops in rotations and biochar use under wetter climate scenarios will allow to reduce nitrate loss and increase soil organic carbon These findings may be used by decision/policy makers working on technologies to mitigate climate change impacts on agriculture and environment